Impact of body composition on pharmacokinetics of doxorubicin in children: a Glaser Pediatric Research Network study - Thompson, Patrick A; Rosner, Gary L; Matthay, Katherine K; Moore, Theodore B; Bomgaars, Lisa R; Ellis, Kenneth J; Renbarger, Jamie; Berg, Stacey L (Cancer chemotherapy and pharmacology, 2009)
Purpose We studied the relationship between doxorubicin pharmacokinetics and body composition in children with cancer. Patients and methods Children between 1 and 21 years of age, receiving doxorubicin as an infusion of any duration <24 h on either a 1-day or 2-day schedule were eligible if they had no significant abnormality of liver function tests, their dose of doxorubicin was not based on ideal body weight or otherwise “capped,” and they weighed >=12 kg. Body composition was measured by dual-energy X-ray absorptiometry. Doxorubicin and doxorubicinol concentration in plasma were measured by high pressure liquid chromatography. NONMEM was used to perform pharmacokinetic model fitting and S-PLUS was used to perform a post hoc analysis to examine the effect of body composition on pharmacokinetic parameters. Results Twenty-two subjects (16 male; 10 Hispanic, 10 Caucasian, 2 Asian) completed the study. The median age was 15.0 years (range 3.3-21.5), median weight was 51.5 kg (range 12.4-80), median BMI was 19.7 (range 13.2-30.0), and median body fat was 25% (range 15-36). The population mean clearance of doxorubicin was 420 ml/min/m². Doxorubicinol but not doxorubicin clearance was lower in patients with body fat greater than 30%. Conclusions Doxorubicinol clearance is decreased in children with >30% body fat. This finding is potentially important clinically, because doxorubicinol may contribute significantly to cardiac toxicity after doxorubicin administration. Further study of the body composition on doxorubicin and doxorubicinol pharmacokinetics and on clinical outcomes is warranted.